2019
DOI: 10.1038/s41598-019-42688-8
|View full text |Cite
|
Sign up to set email alerts
|

DNA insecticide developed from the Lymantria dispar 5.8S ribosomal RNA gene provides a novel biotechnology for plant protection

Abstract: Having observed how botanicals and other natural compounds are used by nature to control pests in the environment, we began investigating natural polymers, DNA and RNA, as promising tools for insect pest management. Over the last decade, unmodified short antisense DNA oligonucleotides have shown a clear potential for use as insecticides. Our research has concentrated mainly on Lymantria dispar larvae using an antisense oligoRING sequence from its inhibitor-of-apoptosis gene. In this arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 44 publications
4
30
0
Order By: Relevance
“…To solve this problem, the development of DNA insecticides (oligonucleotide insecticides, or olinscides) is a promising direction of research [ 2 , 14 , 15 , 16 ]. The concentrations of modern chemical insecticides (organic xenobiotics) in ecosystems could be reduced by using DNA insecticides, which act on and are metabolized by ubiquitous DNAses [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…To solve this problem, the development of DNA insecticides (oligonucleotide insecticides, or olinscides) is a promising direction of research [ 2 , 14 , 15 , 16 ]. The concentrations of modern chemical insecticides (organic xenobiotics) in ecosystems could be reduced by using DNA insecticides, which act on and are metabolized by ubiquitous DNAses [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…To solve this problem, the development of DNA insecticides (oligonucleotide insecticides, or olinscides) is a promising direction of research [ 2 , 14 , 15 , 16 ]. The concentrations of modern chemical insecticides (organic xenobiotics) in ecosystems could be reduced by using DNA insecticides, which act on and are metabolized by ubiquitous DNAses [ 15 ]. Using short antisense fragments from the conserved regions of the genes of insect pests opens the possibility of using this approach when resistance to conventional insecticides occurs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our past research with insects, 11-mer ASOs were found to be the most effective and produced optimal effects [44][45][46][47][48][49][50], which is why we used 11-mer phosphorothioate-modified Cytos-11 without methoxyethyl protection. To study its effects, it was administered twice a week for 21 days in a volume of 0.05 mL (3.5 mg/mL) via subplantar injection, followed by evaluation of the effects on the state of the joint and the concentration of TNF-α.…”
Section: Discussionmentioning
confidence: 99%